Pengaruh Penkes Dan Simulasi P3K Terhadap Pengetahuan dan Keterampilan Menangani Cedera Ankle Strain Pada Anggota Taekwondo - Iffah Khairunnisa; Nurul Fatwati Fitriana (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
ABSTRAKKeywords:Cigarette Consumption, Teenage Students Nutrition StatusObjective: to know the effectof health education and simulation of handling ankle strain.Method: This was a quantitative research with a pre-experimental design and one group pre-test-post-test approach. The population and sample in this study amounted to 37 respondents who were taken using an accidental sampling technique.Results: The average score of knowledge obtained from 37 respondents before given health education was 8.97 and it became 15.03 after the health education was done. The average score of the skills before and after doing the simulation was 4.97 and 8.97 respectively. Wilcoxon test results on the knowledge variable indicated that Z value 5,331 and p value = 0.001, while that on the skill variable showed that Z value 5,391 and p value = 0,000. There are differences in respondent's knowledge and skills before and after health education and simulation.Conclusion: There is an effect of health education and the simulation of first aid on the knowledge and skills of Taekwondo members